Pengaruh Pemberian Pupuk Cair Urin Kambing Etawa terhadap Pertumbuhan Bawang Merah - Nurlaila Sitepu (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the effect of giving urine liquid fertilizer Etawa on the growth of shallots (Allium ascalonicum L.). The research method used was an experiment using a completely randomized design (CRD), consisting of 5 treatments and 4 replications, namely treatment A (0 ml of goat urine / polybag), treatment B (50 ml of goat urine / polybag), treatment C (100 ml of goat urine / polybag), D treatment (150 goat urine / polybag), E treatment (200 ml / l goat urine / polybag). Observations were made on red onion plant height, wet western tubers, number of tubers, and tuber diameter. The results of the study, F count 1.38 < F table 3.06 (5%), wet weight F count 0.8 < F table 3.06 (5%), number of tubers F count 0.5 < F table 3. 06 (5%), and diameter of shallot bulbs F count 0.51 < F table 3.06 (5%). Conclusion, the administration of liquid urine fertilizer Etawa goat did not affect the height of the shallot plant Keywords: etawa goat urine, shallots